The Importance of Polymers in the Preparation of Biomaterials for Removal of Metal and Control of Bacterial Infections for Healthcare Applications - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Salfate-Calderon, G (Elsevier, 2022)
Functionalized polysaccharides such as cellulose, chitosan, and alginate are very important materials, owing to their potential applications in water remediation, metal ions removal, and biomedicine. Polysaccharides have been used in areas such as tissue engineering, implants, medical devices, artificial organs, ophthalmology, dentistry, and bone repair, among others. The first part of this chapter is focused on the ability of these functional polysaccharides to remove metal ions, using both solid-liquid separation techniques and the combination of water-soluble polysaccharide adsorbents with ultrafiltration membranes. The reported literature reveals that the efficiency of metal ion removal depends on various factors, such as the type of functional group present in the polymer, the pH, and the concentration of polymer and metal ions. In general, complex formation and electrostatic interaction are proposed to explain the metal ion uptake. The second part of the chapter is related to the potential application of polysaccharides with metals and metal oxide nanoparticles as antimicrobial wound dressings. These biopolymer-metal materials improve the healing rate of wounds and exert biocide activity against bacteria, fungi, and cancer cells. Those properties depend on the type of polysaccharide used, the type and form of metal involved (ionic, metallic, or metal oxide), and the size of the polysaccharide-metal composites. The metals and metal oxides reviewed in this section include silver, copper, titanium, and zinc. © 2022 Elsevier Ltd. All rights reserved.